Development of trident (tidal resource investigation, device and energy tool) as a rapid evaluation system for tidal in-stream energy resource assessment, power estimation, energy projection and technology matching. - Abundo, Michael Lochinvar Sim (Asean Engineering Journal)
A Matlab-based rapid evaluation software called Tidal Resource Investigation, Device and Energy Tool (TRIDEnT) was developed. TRIDEnT aims to serve as a useful tool for tidal energy resource assessment for selected Philippine coastal waters. With this tool, the user can easily evaluate potential sites where turbine-based power generators could be installed. At the backend lies extensive simulation runs performed using DELFT3D model developed by Deltares which is a sophisticated hydrodynamic model used to study water velocities and other physico-chemical conditions. Based from these simulation data, the program returns the theoretical power that could be extracted at the user-specified area and time frame. Moreover, other valuable data can be provided by the program such as the water velocity within a region as well as how often it reaches a particular threshold value. Such information gives the user the ability to evaluate and compare multiple sites at the same time, which is particularly useful during site-feasibility assessment stages. Lastly, the software was constructed in such a way that sophisticated optimization algorithms can be easily incorporated which would allow real-time optimization of parameters given certain criteria and constraints set by the user.